KETAHANAN DEFORMASI PERMANEN CAMPURAN BERASPAL PANAS LAPIS AC-BC MENGGUNAKAN LIMBAH BETON MUTU K-250 - galih wulandari subagyo (Universitas Trisakti, 2020)
There is a program regarding the Sustainable Development Goals (SDGs) for the period 2015-2030. These Sustainable Development Goals are also a continuation of the Millennium Development Goals (MDGs) which were agreed upon in 2000 and ended in 2015. Of the 17 existing points, they are related to sustainability. The Development Goals contain one of the points that discusses responsible consumption and production, where this point is included in point 12. Thus by 2030 Indonesia has a target that can achieve sustainable management and efficient use of natural resources. This is the basis of this study, where in this study using concrete to be a coarse substitution with a variation of concrete waste using 0%, 5%, 10%, 15% of the total new aggregate. Then carried out on the test object with the Marshall test method to the permanent deformation test so that the Marshall test results and the results of the permanent deformation are obtained. Concrete waste originating from K-250 quality concrete (ex-test with compressive strength) meets the requirements for hot asphalt mix aggregate based on the 2010 Highways Specification (Revision 3). The permanent deformation value of the Asphalt Concrete Binder Course layer mixture that uses K-250 quality concrete waste shows the level of concrete waste with a composition of 5% which has almost the same dynamic stability performance and speed when compared to 0% composition of concrete waste using 10% concrete waste. and 15% for the composition shows lower performance compared to 0% waste concrete.